2019
DOI: 10.1128/aac.00299-19
|View full text |Cite
|
Sign up to set email alerts
|

Nitroglycerin-Citrate-Ethanol Catheter Lock Solution Is Highly Effective for In Vitro Eradication of Candida auris Biofilm

Abstract: Candida auris poses emerging risks for causing severe central lineassociated bloodstream infections. We tested in vitro the ability of antifungal lock solutions to rapidly eradicate C. auris biofilms. Liposomal amphotericin B, amphotericin B deoxycholate, fluconazole, voriconazole, micafungin, caspofungin, and anidulafungin failed to completely eradicate all 10 tested C. auris biofilms. Conversely, nitroglycerin-citrate-ethanol (NiCE) catheter lock solution completely eradicated all replicates for all of C. au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…On the other hand, nitric oxide (NO), a natural product of the immune system, acts as a broad-spectrum antimicrobial agent. In fungi, the NO has shown efficacy against C. auris [12,101]. Cleare et al, 2020 demonstrated the effectiveness of NO nanoparticles (NAC-SNO-np) against six C. auris clinical isolates.…”
Section: Alternative Treatment Strategies In C Aurismentioning
confidence: 99%
“…On the other hand, nitric oxide (NO), a natural product of the immune system, acts as a broad-spectrum antimicrobial agent. In fungi, the NO has shown efficacy against C. auris [12,101]. Cleare et al, 2020 demonstrated the effectiveness of NO nanoparticles (NAC-SNO-np) against six C. auris clinical isolates.…”
Section: Alternative Treatment Strategies In C Aurismentioning
confidence: 99%
“…Although there is increasing recognition that antibiotic lock solutions can reduce the risk of catheter-related bacterial infections, there is no approved antifungal lock therapeutic protocol in clinical practice so far. Vargas-Cruz et al (2019) reported that liposomal amphotericin B, amphotericin B deoxycholate, fluconazole, voriconazole, micafungin, caspofungin, and anidulafungin failed to completely eradicate C. auris biofilms, contraindicating their mono-therapeutic use in lock therapy [ 23 ]. Therefore, certain non-antifungal agents alone or in combination with traditional antifungals have been investigated as a potential approach to overcome C. auris -related catheter-associated infections.…”
Section: Discussionmentioning
confidence: 99%
“…Taurolidine showed moderate activity against biofilms and only partially eradicated sessile populations. Conversely, the minocycline-EDTA-ethanol lock solution and nitroglycerin-citrate-ethanol combination completely eradicated C. auris biofilms in vitro [ 23 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The multidrug resistance phenotype is a well-known characteristic for C. auris; it may be more pronounced in biofilms and further complicate treatment [6]. Based on previous susceptibility testing, amphotericin B, fluconazole, voriconazole, anidulafungin, micafungin and caspofungin could not completely eradicate C. auris biofilms in vitro, increasing the need for effective combination therapies [39]. Certain non-antifungal agents in combination with traditional antifungal drugs have been tested to eradicate C. auris biofilms with variable efficacy [21,22,40].…”
Section: Discussionmentioning
confidence: 99%